2016
DOI: 10.1016/j.ssci.2016.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Modelling social identification and helping in evacuation simulation

Abstract: Social scientists have criticised computer models of pedestrian streams for their treatment of psychological crowds as mere aggregations of individuals. Indeed most models for evacuation dynamics use analogies from physics where pedestrians are considered as particles. Although this ensures that the results of the simulation match important physical phenomena, such as the deceleration of the crowd with increasing density, social phenomena such as group processes are ignored. In particular, people in a crowd ha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(49 citation statements)
references
References 40 publications
(50 reference statements)
1
46
0
2
Order By: Relevance
“…Table 5 lists the strategies for faster access for each setup and point in time. • Pushing and shoving (7) • Turning to the right hand side (6) • Staying on the left hand side (5) Social norms: Participants apply the following social norms to both setups:…”
Section: Inappropriate Behaviormentioning
confidence: 99%
See 2 more Smart Citations
“…Table 5 lists the strategies for faster access for each setup and point in time. • Pushing and shoving (7) • Turning to the right hand side (6) • Staying on the left hand side (5) Social norms: Participants apply the following social norms to both setups:…”
Section: Inappropriate Behaviormentioning
confidence: 99%
“…In using such models, the two setups in our study would have to be treated separately by manually adjusting the intended velocity. However, in order to predict the differences between the two setups and the occurrence of queuing a model is needed which starts one step earlier and treats intended velocity as a quantity which has to be modeled itself, as in [6,64]. From the results presented here, this additional step in modeling must go beyond merely considering physical characteristics and needs to integrate subjective perception and associated strategies and social norms.…”
Section: Semicircle Corridormentioning
confidence: 99%
See 1 more Smart Citation
“…Alvear et al [16] identified three purposes of evacuation models: (a) performance-based analysis for new and existing buildings in order to evaluate the design and evacuation procedures (e.g., [17,18]), (b) forensic analysis to reconstruct historical evacuation processes in order to analyze possible failures and inefficiencies (e.g., [19]), and (c) management during evacuation procedures (e.g., [20]). The detailed assessments of the existing modeling approaches and simulation models can be found in the literature [21][22][23][24].…”
Section: Evacuation Models and Crowd Dynamicsmentioning
confidence: 99%
“…Zheng et al [22] identified two reasons that may cause people being injured or killed during evacuations: either due to failing to evacuate timely, or due to the crowd's behavior such as shuffling, pushing, crushing, and trampling. Sivers et al [19] argued that most models for evacuation dynamics consider individuals as particles, so they added social identity to pedestrian simulation. They take helping others as an example to investigate whether psychological models and computer models of pedestrian motion can be combined so that simulation results correspond to observations from crowd psychology.…”
Section: Evacuation Models and Crowd Dynamicsmentioning
confidence: 99%